1999
DOI: 10.1038/sj.ejhg.5200263
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for the organisation of the four sarcoglycans proteins within the dystrophin–glycoprotein complex

Abstract: Based on the pattern of distribution of the SG proteins in patients withLGMD2C and 2D, and on the observed decreased abundance of dystrophin through WB in some sarcoglycans (SG) patients, we have recently suggested that α, and δ subunits of sarcoglycan complex might be more closely associated and that γ-SG might interact more directly with dystrophin. Two additional SG patients here reported give further support to these suggestions: an LGMD2F patient showed patchy labelling for γ-SG, despite the lack of stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Several studies obtained from single biopsies in human patients showed that the primary mutations in one sarcoglycan is not necessarily associated with the complete loss of the entire sarcoglycan complex. 11,126 In regard to these findings, Vainzof et al 126 suggested that ␣-, ␤and ␦-sarcoglycan might be more closely associated with each other and that ␥-sarcoglycan might interact more directly with dystrophin. In contrast, in vitro studies in myotubes by Chan et al 28 suggested that ␤-, ␥-, and ␦sarcoglycan are more closely associated to one another than ␣-sarcoglycan and that ␦-sarcoglycan tightly binds to dystroglycan.…”
Section: S a R C O G L Y C A N O P A T H I E S A N D T H E S A R C O mentioning
confidence: 99%
“…Several studies obtained from single biopsies in human patients showed that the primary mutations in one sarcoglycan is not necessarily associated with the complete loss of the entire sarcoglycan complex. 11,126 In regard to these findings, Vainzof et al 126 suggested that ␣-, ␤and ␦-sarcoglycan might be more closely associated with each other and that ␥-sarcoglycan might interact more directly with dystrophin. In contrast, in vitro studies in myotubes by Chan et al 28 suggested that ␤-, ␥-, and ␦sarcoglycan are more closely associated to one another than ␣-sarcoglycan and that ␦-sarcoglycan tightly binds to dystroglycan.…”
Section: S a R C O G L Y C A N O P A T H I E S A N D T H E S A R C O mentioning
confidence: 99%
“…88,89 Western blot analysis of muscle usually shows dystrophin with a normal molecular weight and quantities within 10% of normal. Histology usually shows marked degeneration and regeneration and severely dystrophic muscle.…”
Section: Diagnosismentioning
confidence: 99%
“…Linkage analysis reveals that some cases of sarcoglycanopathy (now termed limb girdle muscular dystrophy type 2C) are linked to chromosome 13q12 and display a deficiency of ␥-sarcoglycan; some SCARMD phenotypes are independent of any mechanism involving the primary gene defect . Human patients with mutations in the ␥-sarcoglycan present lower levels of dystrophin, ␣and ␤-sarcoglycan, and disrupted laminin patterns, thus showing that abnormalities of dystrophin may, in some cases, be a secondary phenomenon (Jones et al, 1998;Vainzof et al, 1999b). Ultrastructural studies in a case of ␥-sarcoglycanopathy (LGMD2C) suggest that loss or reduction of the sarcoglycans results in an instability in the plasma membrane, which becomes abnormally indented and convoluted (Hassoni and Cullen, 1999).…”
Section: Sarcoglycan Complexmentioning
confidence: 99%